A comparative study of negative pressure dressing and conventional dressing in lower limb ulcers - Shah, Vishal S.; Prajapati, Narendra K.; Ponkiya, Dhruven H. (International Surgery Journal, 2021)
Background: Lower limb ulcer is a common disease among the Indian population with a prevalence of approximately 1% to 2% which is slightly higher in the older population. There are various modalities of treatment with the main aim being early wound healing. This study is done to compare the results of negative pressure dressing and conventional dressing in lower limb ulcers. Methods: This study, done at the Department of Surgery, G. K. General Hospital and Gujarat Adani Institute of Medical Sciences, Bhuj, from October 2017 to September 2018 is a prospective study. A total of 120 patients were randomly divided in two group comprising of 60 patients each. The patients in Group A were treated with negative pressure dressing while those in Group B were treated with conventional dressing. The patients were assessed, in both test and control groups, with parameters like appearance of granulation tissue, bacterial clearance and wound healing. Results: 80% of the patients belonged to the age group of 41-60 years while others were less than 40 years. We observed that in Group A majority of the patients had wound healing in 11-40 days while in Group B majority patients took 31-60 days for their wounds to be healed. Conclusions: We conclude that negative pressure dressing is more efficient as compared to conventional dressing for healing of lower limb ulcers, enabling a shorter hospital stay and early resumption of daily activities to the patient.